Qualidade fisiológica e sanitária de sementes de soja produzidas em diferentes épocas de semeadura em terras baixas - (:unkn) unknown (Universidade Federal do Pampa, 2019)
Good seed quality is na extremely importante fator for the succes of any crop, characterized by characteristic of genetic, physiological quality and others. By comparing the soybean cultivation cycle used and observing that the maturation and harvesting season with rainfall in a specific region, it is possible to observe changes in the quality of the seeds produced. The negative effect of the environment can be partly controlled by sowing scheduling so that ripening and harvesting take place under favorable climatic conditions. Therefore, this work aims to evaluate the physiological quality of seeds of different soybean cultivars, cultivated at different times, seeking to characterize the physiological effect that can generate on germination, seedling development and seed health.For this, five soybean cultivars with different degrees of relative maturity were used in three treatments (sowing dates) and three replications. The tests were performed in the laboratory, with the monitoring of physiological (germination test, seedling length, seedling weight) and sanitaty measurements. For analysis of variance, Scott and Knott were used at 5% probability, with the aid of the computer proggram Genes. As a result it was observed that seed quality was directly influenced by edaphoclimatic elements at the end of their cycle, as well as their storage period in the laboratory. Thus, it was possible to observe that the third season presented the best results for physiological and sanitary quality, due to the low temperatures and moderate precipitation durin the end of its cycle and harvest.
Keywords: Glycine max.; Épocas de semeadura; Qualidade sanitária e fisiológica de sementes; Sowing times; Seed health and physiological quality; CNPQ::CIENCIAS AGRARIAS